YOUNG LEARNERS’ VOCABULARY AND QUIZLET APPLICATION - Sudrajat, Indra; Pratama, Reza Fatwa (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2022)
This research is about using Quizlet as a learning media to help young learners learn vocabulary and young learners' responses after learning English vocabulary using Quizlet application. This research was conducted in a house in Gadobangkong Village, West Bandung regency. The participants in this study were three young students in the fourth grade of elementary school where they were aged nine to ten years and the researcher as a teacher who taught English vocabulary using the Quizlet application. This study uses a qualitative descriptive analysis with a case study as the research design. The results of the study, there are four memory strategies for each feature provided by Quizlet. Memory Strategy is a learning strategy that involves four sets of memory strategies, namely: creating mental linkages, applying images and sounds, reviewing well, and employing action. The four memory strategies are applied in learning vocabulary using Quizlet. Quizlet has several features that young learners explore during the teaching and learning process. These features include flashcard, learn, write, spell, test, games (matching and gravity) which of the four strategies are applied in learning using Quizlet, but the application of action does not have much effect in this study. And in the "Spell" feature is a feature that is difficult for young learners because they are still lacking in spelling vocabulary letters. Young Learners have a positive response when Quizlet is used in learning English vocabulary. They find Quizlet easy and fun, interesting because Quizlet contains interesting pictures and features, sounds, and games.